Air-stable sulfide solid electrolyte as well as preparation method and application thereof

By employing a dual-element doping and high-temperature sintering method based on the chemical formula Li5.4P1-xS4.4MxCl1.6-yXy, the problems of air stability and ionic conductivity of sulfide solid electrolytes were solved, achieving stability and low-cost production under high humidity conditions, making it suitable for all-solid-state lithium batteries.

CN121097189APending Publication Date: 2025-12-09HUNAN ENERGY FRONTIERS NEW MATERIALS TECH CO LTD

Patent Information

Application Number
CN202511306396.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-06-26
Filing Date
2025-09-12
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing sulfide solid electrolytes have poor chemical stability in air, resulting in high production equipment costs and complex processes. Furthermore, conventional doping methods may sacrifice ionic conductivity or introduce other problems.

Method used

Using the chemical formula Li5.4P1-xS4.4MxCl1.6-yXy, a sulfide solid electrolyte that is stable in air was prepared by dual-element doping (M is selected from Fe, Zn, Ge, Zr, Sn, Ca, Mg, Ti or Ag, and X is selected from F, Br, I) combined with high-temperature sintering and mechanical grinding.

Benefits of technology

It achieves improved stability of ionic conductivity and air stability in high humidity environments, reduces production costs, and is suitable for mass production and all-solid-state battery applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121097189A_ABST
    Figure CN121097189A_ABST
Patent Text Reader

Abstract

The invention discloses an air-stable sulfide solid electrolyte as well as a preparation method and application thereof, and relates to the technical field of solid-state lithium batteries. The chemical formula of the sulfide solid electrolyte is Li < 5.4 > P < 1-x > S < 4.4 > M < x > Cl < 1.6-y > X < y >, x is greater than 0 and less than 0.08, y is greater than 0 and less than 1, and M is selected from at least one of Fe, Zn, Ge, Zr, Sn, Ca, Mg, Ti or Ag; x is selected from at least one of F, Cl, Br and I. According to the sulfide solid electrolyte disclosed by the invention, through double-element doping of metal elements and halogen, the surface energy of a material is reduced, water molecule adsorption is inhibited, meanwhile, the ionic conductivity of the sulfide solid electrolyte can be obviously improved, and the conductivity of the sulfide solid electrolyte is not obviously attenuated in a high-humidity environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of solid-state lithium battery technology, and in particular to an air-stable sulfide solid electrolyte, its preparation method, and its application. Background Technology

[0002] With the rapid development of new energy vehicles and the energy storage industry, high-energy-density, high-safety all-solid-state lithium batteries (ASSBs) have become the core direction of next-generation battery technology. As a core component of all-solid-state batteries, solid electrolytes need to simultaneously meet requirements such as high ionic conductivity, wide electrochemical window, mechanical stability, and environmental compatibility. Sulfide solid electrolytes, with their ultra-high lithium-ion mobility (up to 10⁻⁶ ions / mL at room temperature), offer a solution. -3 ~10 -2 Due to its low interfacial impedance (S / cm) and low interfacial impedance with electrode materials, it has become one of the most promising solid electrolyte categories.

[0003] With Li7P3S 11 Sulfide-silver germanium mineral materials, such as Li6PS5Cl, have achieved ion conductivity comparable to liquid electrolytes and have shown significant advantages in fast charging and wide-temperature applications. However, sulfide solid electrolytes face a fatal flaw in practical applications: their extremely poor chemical stability in air. When exposed to environments containing trace amounts of moisture, sulfide electrolytes undergo rapid hydrolysis (e.g., Li3PS4 + H2O → Li2S + H2S↑ + LiH2PO4), leading to material pulverization, decreased ion conductivity, and the release of toxic gases. Experiments show that after exposure to air with humidity >10% for 5 minutes, the ion conductivity of typical sulfide solid electrolytes decreases by more than 80%, and interfacial side reactions further exacerbate the deterioration of battery cycle performance. This characteristic necessitates that the manufacture of sulfide batteries must be carried out under strictly dry conditions (dew point < -40℃) or inert atmospheres (such as argon glove boxes), resulting in high production equipment costs and complex processes, severely hindering their large-scale commercialization.

[0004] To improve the chemical stability of sulfide solid electrolytes in air, existing technologies mainly include elemental doping / substitution, surface coating, and composite electrolytes. However, conventional elemental doping / substitution methods often sacrifice ionic conductivity (e.g., conductivity decreases by 1-2 orders of magnitude after oxygen doping); surface coating processes are complex and it is difficult to achieve a uniform and dense protective layer; while composite electrolyte systems face problems such as a surge in interfacial impedance and a decrease in volumetric energy density. Among these, elemental doping / substitution, through atomic-level control, can solve the sulfide stability problem intrinsically, and its low processing cost makes it one of the core strategies for improving the air stability of sulfide solid electrolytes. To meet the requirements of both high ionic conductivity and long-term stability in air for sulfide electrolytes, it is urgent to develop a solution that improves their air tolerance without sacrificing intrinsic material properties.

[0005] Patent CN119518076A describes a high-density sulfide solid electrolyte, which combines raw materials LiS and P2O5 with modified sulfide dopants. The modified sulfide dopants are one or more sulfides selected from Zr, Sn, and In. The mixture is sintered and ground to obtain the sulfide solid electrolyte. This method allows for sufficient contact between the raw materials and significantly improves the crystallinity of the sulfide solid electrolyte, thereby increasing its ionic conductivity. However, it fails to simultaneously improve both the air stability and ionic conductivity of the sulfide electrolyte. Summary of the Invention

[0006] To address the shortcomings of existing solid electrolytes, a sulfide solid electrolyte is provided that can simultaneously improve the air stability and ionic conductivity of sulfide electrolytes.

[0007] Another object of the present invention is to provide a method for preparing a sulfide solid electrolyte.

[0008] Another object of the present invention is to provide an application of the above-mentioned sulfide solid electrolyte in the preparation of all-solid-state lithium batteries.

[0009] This invention protects a sulfide solid electrolyte with the chemical formula Li. 5.4 P 1-x S 4.4 M x Cl 1.6-y X y ;0<x<0.08, 0<y<1, In the formula, M is selected from at least one of Fe, Zn, Ge, Zr, Sn, Ca, Mg, Ti or Ag; X is selected from at least one of F, Br, and I.

[0010] Preferably, M is selected from Zr and / or Sn, more preferably Sn.

[0011] Preferably, X is selected from F and / or Br, more preferably Br.

[0012] In some embodiments, the Li 5.4 P 1-x S 4.4 M x Cl 1.6-y X y In the given condition, 0.01≤x≤0.06, 0.6≤y≤0.85. Preferably, 0.02≤x≤0.045, and more preferably 0.024≤x≤0.04.

[0013] Preferably, 0.65≤y≤0.85, more preferably 0.7≤y≤0.82.

[0014] In some embodiments, the chemical formula is Li 5.4 P 1-x S 4.4 Sn x Cl 1.6-y Br y , 0.025≤x≤0.04, 0.7≤y≤0.8.

[0015] This invention protects a method for preparing a sulfide solid electrolyte, comprising the following steps: S1, take Li2S, P2S5, LiCl raw materials and dopants, mix them and mechanically grind them to obtain precursor materials; The dopant is a sulfide metal salt and a halide lithium salt, wherein the metal element in the sulfide metal salt is selected from at least one of Fe, Zn, Ge, Zr, Sn, Ca, Mg, Ti or Ag; and the halogen in the halide lithium salt is selected from at least one of F, Br, I. S2, the precursor material is sintered at high temperature and then cooled to obtain the sulfide solid electrolyte.

[0016] Preferably, the sulfide metal salt is selected from SnS2 and / or ZrS2. Preferably, the halide lithium salt and / or LiBr and / or LiF.

[0017] In some embodiments, in step S1, the stoichiometric ratio of Li2S, P2S5, LiCl, sulfide metal salt and halide lithium salt is 4:1:3.2-Y:X:Y; and 0 < X ​​< 0.06, 1 < Y ​​< 2; Preferably, 0.01 ≤ X ≤ 0.6; more preferably, 0.025 ≤ X ≤ 0.4.

[0018] Preferably, 1.2 ≤ Y ≤ 1.7; more preferably, 1.4 ≤ Y ≤ 1.6.

[0019] In some embodiments, the ball-to-material ratio in the mechanical grinding of step S1 is (20-60):1.

[0020] In some embodiments, the mechanical grinding in step S1 includes a first-stage grinding and a second-stage grinding; The grinding speed of the first stage is 400-600 r / min, and the ball milling time is 0.5-3 h; The two-stage grinding process involves a rotation speed of 600-1000 r / min and a ball milling time of 0.5-3 h.

[0021] In some embodiments, the mechanical grinding unit is any one of a high-speed mixer, a planetary ball mill, a horizontal ball mill, or an air jet mill.

[0022] In some embodiments, in step S2, the sintering temperature is 400-600℃ and the sintering time is 6-10 h.

[0023] In some embodiments, the preparation method of the present invention is carried out in an inert gas atmosphere.

[0024] Optionally, the inert gas is argon and / or nitrogen.

[0025] This invention protects the application of a sulfide solid electrolyte in the preparation of all-solid-state lithium batteries.

[0026] An all-solid-state lithium battery includes a positive electrode, a negative electrode, and a sulfide solid electrolyte.

[0027] Compared with the prior art, the beneficial effects of the present invention are: The present invention discloses a sulfide solid electrolyte, which is a LiPSCl-type electrolyte with dual-element doping of metal elements and halogens. The synergistic effect of the dual elements reduces the surface energy of the material to inhibit water molecule adsorption, while significantly improving its ionic conductivity. Moreover, its conductivity does not decrease significantly under high humidity conditions.

[0028] This invention discloses a method for preparing a sulfide solid electrolyte, which achieves dual-element doping based on a weak acid substitution method, generating a weakly acidic doped phase in situ. This maintains the structural integrity of the sulfide matrix and is less prone to component segregation. Furthermore, by utilizing high-temperature solid-state sintering and mechanical grinding, a high-purity sulfide solid electrolyte with good microstructure and stable properties at room temperature can be obtained. This preparation method effectively reduces the cost of sulfide solid electrolyte production processes, promotes the large-scale mass production of sulfide solid electrolytes, and enables the application of all-solid-state batteries in vehicles. Attached Figure Description

[0029] Figure 1The images show the XRD patterns of the sulfide solid electrolytes of Examples 1-3 and Comparative Example 1 of this invention.

[0030] Figure 2 This is a SEM image of the sulfide solid electrolyte of Example 1 of the present invention.

[0031] Figure 3 This is the EDS energy spectrum of the sulfide solid electrolyte of Example 1 of the present invention.

[0032] Figure 4 This is the electrochemical impedance spectroscopy of the sulfide solid electrolyte of Example 1 of the present invention. Detailed Implementation

[0033] The present invention will be further described below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise stated, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0034] Example 1 A method for preparing a sulfide solid electrolyte, comprising the following steps under an argon atmosphere: (1) Weigh a certain amount of Li2S, P2S5, LiCl raw materials and SnS2, LiBr dopants in a stoichiometric ratio of 4:1:1.8:0.025:1.4. Place the materials in a sealed ball mill jar with a ball-to-material ratio of 30:1. Perform the first ball milling using mechanical ball milling at a speed of 500 r / min for 1 h. After thorough slaking, sieve the mixture and transfer it to the ball mill jar for the second ball milling at a speed of 800 r / min for 1 h. The ground sulfide solid electrolyte precursor is obtained by sieving.

[0035] (2) The sulfide solid electrolyte precursor was sintered in a muffle furnace at 500°C for 8 hours, and then cooled to room temperature to obtain the sulfide solid electrolyte with the chemical formula Li. 5.4 P 0.975 S 4.4 Sn 0.025 Cl 0.9 Br 0.7 .

[0036] Example 2 A method for preparing a sulfide solid electrolyte, comprising the following steps under an argon atmosphere: (1) Weigh a certain amount of Li2S, P2S5, LiCl raw materials and SnS2, LiBr dopants according to a stoichiometric ratio of 4:1:2:0.01:1.2. Place the materials in a sealed ball mill jar with a ball-to-material ratio of 30:1. Perform the first ball milling using mechanical ball milling at a speed of 500 r / min for 1 h. After thorough slaking, sieve the mixture and transfer it to the ball mill jar for the second ball milling at a speed of 800 r / min for 1 h. The ground sulfide solid electrolyte precursor is obtained by sieving.

[0037] (2) The sulfide solid electrolyte precursor was sintered in a muffle furnace at 500°C for 8 hours, and then cooled to room temperature to obtain the sulfide solid electrolyte with the chemical formula Li. 5.4 P 0.99 S 4.4 Sn 0.01 ClBr 0.6 .

[0038] Example 3 A method for preparing a sulfide solid electrolyte, comprising the following steps under an argon atmosphere: (1) Weigh a certain amount of Li2S, P2S5, LiCl raw materials and SnS2, LiBr dopants in a stoichiometric ratio of 4:1:1.6:0.04:1.6. Place the materials in a sealed ball mill jar with a ball-to-material ratio of 30:1. Perform the first ball milling using mechanical ball milling at a speed of 500 r / min for 1 h. After thorough slaking, sieve the mixture and transfer it to the ball mill jar for the second ball milling at a speed of 800 r / min for 1 h. The ground sulfide solid electrolyte precursor is obtained by sieving.

[0039] (2) The sulfide solid electrolyte precursor was sintered in a muffle furnace at 500°C for 8 hours, and then cooled to room temperature to obtain the sulfide solid electrolyte with the chemical formula Li. 5.4 P 0.96 S 4.4 Sn 0.04 Cl 0.8 Br 0.8 .

[0040] Example 4 A method for preparing a sulfide solid electrolyte, comprising the following steps under an argon atmosphere: (1) Weigh a certain amount of Li2S, P2S5, LiCl raw materials and SnS2, LiBr dopants in a stoichiometric ratio of 4:1:1.8:0.06:1.4. Place the materials in a sealed ball mill jar with a ball-to-material ratio of 30:1. Perform the first ball milling using mechanical ball milling at a speed of 500 r / min for 1 h. After thorough slaking, sieve the mixture and transfer it to the ball mill jar for the second ball milling at a speed of 800 r / min for 1 h. The ground sulfide solid electrolyte precursor is obtained by sieving.

[0041] (2) The sulfide solid electrolyte precursor was sintered in a muffle furnace at 500°C for 8 hours, and then cooled to room temperature to obtain the sulfide solid electrolyte with the chemical formula Li. 5.4 P 0.94 S 4.4 Sn 0.06 Cl 0.9 Br 0.7 .

[0042] Example 5 A method for preparing a sulfide solid electrolyte, differing from Example 1 in that SnS2 in Example 1 is replaced with an equimolar amount of ZrS2; the method includes the following steps: (1) Weigh a certain amount of Li2S, P2S5, LiCl raw materials and ZrS2, LiBr dopants in a stoichiometric ratio of 4:1:1.8:0.025:1.4. Place the materials in a sealed ball mill jar with a ball-to-material ratio of 30:1. Perform the first ball milling using mechanical ball milling at a speed of 500 r / min for 1 h. After thorough slaking, sieve the mixture and transfer it to the ball mill jar for the second ball milling at a speed of 800 r / min for 1 h. The ground sulfide solid electrolyte precursor is obtained by sieving.

[0043] (2) The sulfide solid electrolyte precursor was sintered in a muffle furnace at 500°C for 8 hours, and then cooled to room temperature to obtain the sulfide solid electrolyte with the chemical formula Li. 5.4 P 0.975 S 4.4 Zr 0.025 Cl 0.9 Br 0.7 .

[0044] Example 6 A method for preparing a sulfide solid electrolyte, differing from Example 1 in that: the LiBr in Example 1 is replaced with an equimolar amount of LiF; the method includes the following steps: (1) Weigh a certain amount of Li2S, P2S5, LiCl raw materials and SnS2, LiF dopants in a stoichiometric ratio of 4:1:1.8:0.025:1.4. Place the materials in a sealed ball mill jar with a ball-to-material ratio of 30:1. Perform the first ball milling using mechanical ball milling at a speed of 500 r / min for 1 h. After thorough slaking, sieve the mixture and transfer it to the ball mill jar for the second ball milling at a speed of 800 r / min for 1 h. The ground sulfide solid electrolyte precursor is obtained by sieving.

[0045] (2) The sulfide solid electrolyte precursor was sintered in a muffle furnace at 500°C for 8 hours, and then cooled to room temperature to obtain the sulfide solid electrolyte with the chemical formula Li. 5.4 P 0.975 S 4.4 Sn 0.025 Cl 0.9 F 0.7 .

[0046] Comparative Example 1 A method for preparing a sulfide solid electrolyte includes the following steps: (1) Weigh a certain amount of Li2S, P2S5 and LiCl raw materials in a stoichiometric ratio of 4:1:3, place the materials in a sealed ball mill jar, and the ball-to-material ratio is 30:1; use mechanical ball milling to perform the first ball milling, the ball milling speed is 500 r / min and the ball milling time is 1 h; after the jar is fully pounded, sieve it and transfer it to the ball mill jar again for the second ball milling, the ball milling speed is 800 r / min and the ball milling time is 1 h, and sieve to obtain the ground sulfide solid electrolyte precursor.

[0047] (2) The sulfide solid electrolyte precursor was sintered in a muffle furnace at 500°C for 8 hours, and then cooled to room temperature to obtain the sulfide solid electrolyte with the chemical formula Li. 5.5 PS 4.5 Cl 1.5 .

[0048] Comparative Example 2 A method for preparing a sulfide solid electrolyte, differing from Example 1 in that the dopant in this comparative example is SnS2; includes the following steps: (1) Weigh a certain amount of Li2S, P2S5, LiCl raw materials and SnS2 dopant according to the stoichiometric ratio of 4:1:3.2:0.025. Place the materials in a sealed ball mill jar with a ball-to-material ratio of 30:1. Perform the first ball milling using mechanical ball milling at a speed of 500 r / min for 1 h. After thorough slaking, sieve the mixture and transfer it to the ball mill jar for the second ball milling at a speed of 800 r / min for 1 h. The ground sulfide solid electrolyte precursor is obtained by sieving.

[0049] (2) The sulfide solid electrolyte precursor was sintered in a muffle furnace at 500°C for 8 hours, and then cooled to room temperature to obtain the sulfide solid electrolyte with the chemical formula Li. 5.4 P 0.975 S 4.4 Sn 0.025 Cl 1.6 .

[0050] Comparative Example 3 A method for preparing a sulfide solid electrolyte, differing from Example 1 in that the dopant in this comparative example is LiBr, includes the following steps: (1) Weigh a certain amount of Li2S, P2S5, LiCl raw materials and LiBr dopant in a stoichiometric ratio of 4:1:1.8:1.4. Place the materials in a sealed ball mill jar with a ball-to-material ratio of 30:1. Perform the first ball milling using mechanical ball milling at a speed of 500 r / min for 1 h. After thorough slaking, sieve the mixture and transfer it to the ball mill jar for the second ball milling at a speed of 800 r / min for 1 h. The ground sulfide solid electrolyte precursor is obtained by sieving.

[0051] (2) The sulfide solid electrolyte precursor was sintered in a muffle furnace at 500°C for 8 hours, and then cooled to room temperature to obtain the sulfide solid electrolyte with the chemical formula Li. 5.4 P 0.975 S 4.4 Cl 0.9 Br 0.7 .

[0052] Comparative Example 4 A method for preparing a sulfide solid electrolyte differs from Example 1 in that: in this comparative example, the dopant LiBr is in excess, and the method includes the following steps: (1) Weigh a certain amount of Li2S, P2S5, LiCl raw materials and SnS2, LiBr dopants in a stoichiometric ratio of 4:1:1.8:0.1:1.4. Place the materials in a sealed ball mill jar with a ball-to-material ratio of 30:1. Perform the first ball milling using mechanical ball milling at a speed of 500 r / min for 1 h. After thorough slaking, sieve the mixture and transfer it to the ball mill jar for the second ball milling at a speed of 800 r / min for 1 h. The ground sulfide solid electrolyte precursor is obtained by sieving.

[0053] (2) The sulfide solid electrolyte precursor was sintered in a muffle furnace at 500°C for 8 hours, and then cooled to room temperature to obtain the sulfide solid electrolyte with the chemical formula Li. 5.4 P 0.9 S 4.4 Sn 0.1 Cl 0.9 Br 0.7 .

[0054] Performance testing 1. XRD characterization The sulfide solid electrolytes of Examples 1-5 and Comparative Examples 1-4 were subjected to XRD (X-ray diffraction) tests, and the results are as follows: Figure 1 As shown.

[0055] from Figure 1 It can be seen that the sulfide solid electrolytes of each embodiment and comparative example have the same characteristic peaks, and the peak positions are not significantly shifted, indicating that the introduction of dopants has little effect on lattice distortion.

[0056] 2. SEM and EDS characterization The sulfide solid electrolyte of Example 1 was analyzed by SEM (scanning electron microscopy) and EDS (energy-dispersive X-ray spectroscopy), and the results are as follows. Figure 2 and Figure 3 As shown; from Figure 2 The SEM morphology shows that the microstructure of the sulfide solid electrolyte particles of the present invention is spherical, which is beneficial to improving the packing density, ionic conductivity and battery rate performance.

[0057] from Figure 3 The EDS spectrum shows that Sn and Br elements were detected in the sulfide solid electrolyte of the present invention, indicating that the dopant was successfully incorporated into the sulfide solid electrolyte.

[0058] 3. Electrochemical performance testing To test the ionic conductivity of the solid electrolyte, a certain mass of sulfide solid electrolytes from each example and comparative example was weighed, pressed into discs with a thickness of 0.15-0.16 cm, placed in a test mold to assemble a mold battery, and the impedance value was tested after being kept at 25°C for 0.5 h; then the impedance value was tested after being placed at a dew point of -30°C for 1 h. The results are shown in Table 1.

[0059] The formula for calculating ionic conductivity is δ = T / C × R, where T is the thickness, C is a constant, and R is the test impedance value. The retention rate of ionic conductivity under high humidity is calculated as the ratio of the ionic conductivity after 1 hour at a dew point of -30°C to the ionic conductivity under sealed conditions. The test impedance value R is determined by electrochemical impedance spectroscopy (EIS) analysis. The EIS analysis of the sulfide solid electrolyte in Example 1 is as follows: Figure 4 As shown.

[0060] Table 1

[0061] As can be seen from Table 1, the sulfide electrolyte of the present invention can simultaneously achieve both air stability and ionic conductivity, with an ionic conductivity of over 9.24 S / cm and a retention rate of over 56.2% of the ionic conductivity under high humidity.

[0062] Compared to Example 1, Comparative Example 1, which did not contain any dopant, exhibited lower ionic conductivity and a conductivity retention rate of less than 45% after air exposure, indicating poor air stability. Comparative Example 2, which only contained SnS2 doping, also showed low ionic conductivity. Comparative Example 3, which used LiBr as a dopant, experienced a decrease in ionic conductivity retention after air exposure, indicating poor air stability. Comparative Example 4, with excessive Sn doping, resulted in a decrease in ionic conductivity.

[0063] The above embodiments of the present invention are merely examples for clearly illustrating the present invention and are not intended to limit the implementation of the present invention. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all possible implementations here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A sulfide solid electrolyte, characterized in that, Its chemical formula is Li 5.4 P 1-x S 4.4 M x Cl 1.6-y X y ; 0 < x < 0.08, 0 < y < 1, In the formula, M is selected from at least one of Fe, Zn, Ge, Zr, Sn, Ca, Mg, Ti or Ag; X is selected from at least one of F, Br, and I.

2. The sulfide solid electrolyte according to claim 1, characterized in that, In the formula, 0.01≤x≤0.06, 0.6≤y≤0.

85.

3. The sulfide solid electrolyte according to claim 1, characterized in that, Its chemical formula is Li 5.4 P 1- x S 4.4 Sn x Cl 1.6-y Br y , 0.025≤x≤0.04, 0.7≤y≤0.

8.

4. A method for preparing the sulfide solid electrolyte according to any one of claims 1-3, characterized in that, Includes the following steps: S1, take Li2S, P2S5, LiCl raw materials and dopants, mix them and mechanically grind them to obtain precursor materials; The dopant is a sulfide metal salt and a halide lithium salt, wherein the metal element in the sulfide metal salt is selected from at least one of Fe, Zn, Ge, Zr, Sn, Ca, Mg, Ti or Ag; and the halogen in the halide lithium salt is selected from at least one of F, Br, I. S2, the precursor material is sintered at high temperature and then cooled to obtain the sulfide solid electrolyte.

5. The method for preparing the sulfide solid electrolyte according to claim 4, characterized in that, In step S1, the stoichiometric ratio of Li2S, P2S5, LiCl, sulfide metal salt and halide lithium salt is 4:1:3.2-Y:X:Y; and 0 < X ​​< 0.06, 0 < Y < 2.

6. The method for preparing the sulfide solid electrolyte according to claim 5, characterized in that, 0.01≤X≤0.06, 1.2≤Y≤1.

7.

7. The method for preparing the sulfide solid electrolyte according to claim 4, characterized in that, In the mechanical grinding process described in step S1, the ball-to-material ratio is (20-60):

1.

8. The method for preparing the sulfide solid electrolyte according to claim 4 or 7, characterized in that, The mechanical grinding in step S1 includes a first-stage grinding and a second-stage grinding; The grinding speed of the first stage is 400-600 r / min, and the ball milling time is 0.5-3 h; The two-stage grinding process involves a rotation speed of 600-1000 r / min and a ball milling time of 0.5-3 h.

9. The method for preparing the sulfide solid electrolyte according to claim 4, characterized in that, In step S2, the sintering temperature is 400-600℃ and the sintering time is 6-10 h.

10. The use of the sulfide solid electrolyte according to any one of claims 1-3 in the preparation of an all-solid-state lithium battery.

Citation Information

Patent Citations

  • High-density sulfide solid electrolyte as well as pressure-maintaining sintering method and application thereof

    CN119518076A

Cited By

  • Oxygen-doped lithium sulfide, sulfide solid electrolyte and preparation method thereof

    CN122585949A